Effectiveness of social media influencers and their impact on customers' attitudes and buying intention - Elmousa, Hadeel; Yee, Wong Foong; Cheah, Jun Hwa (Inderscience Publishers, 2024)
This research aims to bridge the industry and literature gaps by corroborating the impact of social media influencers on consumer attitudes and intentions towards promotions. A total of 350 responses were acquired through the purposive sampling method. The selected approach for testing the hypotheses was partial least squares (PLS). The observations corroborated the model by substantiating that source credibility, subjective norms, and meaning transfer were significantly related to attitude. Furthermore, source credibility, attitude, and subjective norms were significantly related to buying intention. From various contexts, this study contributes to the marketing literature and sector. First, this work employed the theory of reasoned action from the psychology domain to demonstrate the association between behaviour and attitude in human activities, which is presently being extended to an influencer marketing situation in Malaysia. Second, the outcomes of this research can offer profound insights and guiding principles for firms, marketing agencies, marketers, and influencers. Copyright © 2024 Inderscience Enterprises Ltd.